Correlation of Leg Muscle Power with Smash Success in Sepak Takraw Athletes - Suhartiwi; Fitra Siu; Marsuna (Universitas Pendidikan Ganesha, 2025)
The purpose of this study is to determine the correlation of leg muscle power with smash success in sepak takraw athletes. This research method is a quantitative correlational approach. The population of this study is all UHO sepak takraw club athletes, totaling 25 people. The sampling technique is based on total sampling, namely, all populations are used as samples, obtained 25 people. The instruments used are a vertical jump test to measure leg muscle power and a smash ability test to measure smash ability. Based on the statistical analysis of the correlation test using the SPSS 21 application, the relationship between the leg muscle power coefficient and smash ability is positive; the calculated r value is 0.540, a significant level of 0.005 <0.05, with a determination coefficient of 0.291 or 29.1%, which means there is a significant relationship between leg muscle power and smash ability. The results of this study, if entered on a correlation map, the relationship between the two variables is in the moderate correlation category. The conclusion in this study is that leg muscle power has a correlation with smash success in sepak takraw athletes.